Knowledge and attitude on pressure ulcer prevention among nursing students in UiTM Selangor Puncak Alam Campus / Roslinda Isa, Nor Adlina Syafiah Zuri Azman, Tuan Nur Amira Tuan Mat - Isa, Roslinda; Zuri Azman, Nor Adlina Syafiah; Tuan Mat, Tuan Nur Amira (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Development of pressure ulcer among patients in healthcare setting can be reduced by improving the knowledge and attitude among nursing students as represented the future generation in prevention of pressure ulcer. This research is aimed to identify knowledge and attitude among nursing students regarding pressure ulcer prevention in UiTM Selangor, Puncak Alam Campus. It also examined the relationships between knowledge and attitude of nursing students related to pressure ulcer prevention. One hundred fifty-seven subjects returned the questionnaires with a 100% rate of response. The respondent was nursing students that studying in UiTM Selangor, Puncak Alam Campus. Study design used was cross-sectional study. The findings revealed that respondent had a very poor knowledge mean 45.4% (SD= 2.362). There was a high score of attitude mean 75.3% (SD=4.597). The finding also found weak correlation between knowledge and attitude (r =.132, p <.01). Nursing students’ knowledge on pressure ulcer prevention was very low. However, most of the respondents showed high attitude scores. From these findings suggest that involvement of nursing students from different institutions to improve the generalization of the results.